Health Record Management System – A Web-based Application - Mishra, Akhilesh; Jaiswal, Anuj; Chaudhari, Lokesh; Bodade, Varsha (Journal of ISMAC, 2022)
Storage of data and using that data in an effective manner are the major issues in the health management system. Security of health data and the use of this data in a proper way are very important. This project of Health Record Management System is a web application-based project designed for the hospital to manage and use the data of their patients effectively. The main aspect of the project is to provide a system where the data can be stored and retrieved easily. The web application is designed from the scratch without any idea involving the existing systems. The project focuses on developing a simple system where the doctor can upload the data of the patient in the system and can retrieve it when needed. The patient can view the same data from their end. Moreover, the patients can book the appointment with the doctor through the application. The final project consists of a website which attains all the features of a management system. Another focus of the project is to develop a web-based application with application rich UI and UX interfaces which is very accessible even for the new users of the technology. The system is also notable for its great user friendliness.